Comparing symptom networks of daytime and nocturnal panic attacks in a community-based sample. (January 2022) - Smith, Nicole S.; Bauer, Brian W.; Capron, Daniel W.
Abstract: Nocturnal panic refers to waking in a state of panic without obvious triggers, experiencing the same symptoms as panic attacks that occur while awake. Interrelationships between daytime and nocturnal panic symptoms have not been examined despite theories suggesting panic symptoms perpetuate one another in a forward feedback loop. The current study compared associations between symptoms in daytime and nocturnal panic using network analysis. Network theory conceptualizes symptoms as causing one another, rather than originating from a latent variable (i.e., a disorder). Given that nocturnal panic originates from sleep stages without cognitive activity, cognitive symptoms were expected to be more central in daytime panic networks than nocturnal panic networks. Prior literature indicates similar nocturnal and daytime panic severity; thus, we expected that panic groups would report equivalent panic symptom severity. An online community sample ( N  = 215) provided panic symptom history. Panic network structures did not differ, although the daytime panic network produced stronger and more numerous connections between physical and cognitive symptoms. The nocturnal panic group, however, reported more severe cognitive symptoms than the daytime panic group. These results challenge biologically-focused nocturnal panic theories and suggest a more significant role of cognitive symptoms in perpetuating nocturnal panic attacks once the individual awakens. Highlights: Daytime and nocturnal panic network structures did not significantly differ. Daytime network showed stronger connections between physical and cognitive symptoms. Nocturnal panic group rated cognitive symptoms more severe than daytime panic group.